Using simulating annealing for the inverse estimation of the non-acoustical parameters of sound absorbers. Issue 4 (December 2017) - Cobo, Pedro; Simón, Francisco
Acoustic characterization of sound absorbing materials requires the measurement of one to five non-acoustical parameters, depending on the assumed impedance model. The measurement of five non-acoustical parameters, in the case of more refined impedance models, is sophisticated and time-consuming. As an alternative, a much simpler measurement of the normal incidence sound absorption in an impedance tube can be carried out, and the non-acoustical parameters can be estimated by minimizing the difference between the measured and modeled absorption curves. This inverse procedure requires the choice of the impedance model and the inversion method. The aim of the article is to review the goodness of simulating annealing for estimating the non-acoustical parameters of Miki and Champoux–Stinson models of two granular absorbers. Three of these non-acoustical parameters, common to the two models, are also measured, so that a comparison between measured and estimated parameters can be performed.